Digitalization, internationalization, and firm performance : A resource-orchestration perspective on new OLI advantages - Bhandari, Krishna Raj; Zámborský, Peter; Ranta, Mikko; Salo, Jari (Elsevier, 2023)
Digital forces and digital global connection weaken traditional ownership, location and internalization (OLI) advantages and intensify new OLI advantages (open resources, linkages and integration). However, by building on the resource-orchestration theory, we raise the question of how digitalization (utilization and orchestration of digital resources) and internationalization (firm-level outward internationalization and country-level inward internationalization) affect firm performance. We introduce the degree of outward internationalization and home-country inward foreign direct investment (FDI) inflows as moderators in achieving firm performance as a result of digitalization. Using a panel dataset of 571 U.S. manufacturing firms, we find a curvilinear relationship between digitalization and performance. The top quartile of digitalization efforts is rewarded by significant profitability. Moreover, high levels of outward internationalization and high net-FDI inflows increase the performance gains attributable to high levels of digitalization. Overall, the resource-orchestration theory complements new OLI advantages in explaining firm performance in the digital world.
Keywords: performance; Digital transformation; Digital resources; Resource orchestration; Resource-based view; New OLI advantages; FDI spillovers; internationalisation; digitalisation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|